Characteristics of Mediastinal Tumors in Dr. Hasan Sadikin General Hospital, Periods of 2011-2016 - Octavianus Giovani; Hasrayati Agustina; Teguh M Djajakusumah (Journal of Medicine and Health, 2018)
Mediastinal tumors are considered to be mediastinal disease with various clinical and histopathologic presentations. In Indonesia, literatures concerning mediastinal tumors are still few. This study aims to obtain the characteristic of mediastinal tumors in Dr.Hasan Sadikin Hospital. A cross-sectional retrospective study was conducted using medical records from 2011 to 2016. All medical records with clinical diagnosis of mediastinal tumors are included, and cases with metastatic tumors from distant sites to the mediastinum, and/or incorrect histopathologic findings are excluded. We obtain data of age, gender, clinical symptoms, histopathologic finding, and staging, with total samples collected of 72. We find out that patients with mediastinal tumors are mainly over 40 years old (62.5%), especially in the 6th decade of life (23.6%), and were mostly of males (73.6%). Patients mainly had chief complaints of dyspnea (38.7%), followed by cough and typical myasthenia gravis symptoms. The most common type of mediastinal tumor is epithelial cell tumor (68.4%), and the most common stage is Masaoka-Koga stage III (37.5%). This study concludes that mediastinal tumor mainly occurs in males aged 40 years old and above, with epithelial cell tumor as the most common histopathologic findings.Keywords : characteristics; mediastinal tumor; mediastinum